Frame‐type kernel and time‐frequency transforms. (1st May 2022) - Chen, Qiuhui; Zhang, Yiqiao
Abstract : Originated from frame theory, the notion of frame‐type kernel is put forward. With the help of positive operators, a parallel theory of frame for time‐frequency integral transforms is established. In view of frame type kernel, the theories of windowed Fourier transform and wavelet transform are revisited. Moreover, some new time‐frequency transforms with nonlinear modulation and frequency varying dilation are designed.